Applied multicriteria methodology under Pythagorean fuzzy environment with FMEA to appraise new product development process. - García Aguirre, Pedro Angel (Universidad Autónoma de Ciudad Juárez, 2024)
New Product Development Process (NPDP) is an important process in the industry, since it helps the global companies to get the expected sales and revenues, because of the launch of new products into the market. Moreover, NPDP is a complex process while requires the involvement of multiple functional areas, where people must be synchronized to execute the project activities, during this long process, different risks appear and can affect the project results, delaying the project launch introducing new products with unexpected defects for customers, reason why the global companies are continuously looking for NPDP improvements, trying to enhance the NPDP risk assessment. This thesis presents the use of Pythagorean fuzzy sets, Dimensional Analysis, Failure Mode and Effect Analysis, and Value Stream Mapping (PFDA-FMEA-VSM), method that have the main objective to disperse the uncertainty during the NPDP risk assessment. Concluding this investigation, it is demonstrated that PFDA-FMEA-VSM is enhancing NPDP making possible to get a strongest NPDP appraisal, while allows to have a clear view of the real risks thru all the NPDP process steps, helping the project stakeholders to take best decisions for the business. The conclusion is as well supported by results published at different pear reviewed scientific journals.